Community Pharmacies in Poland—The Journey from a Deregulated to a Strictly Regulated Market - Wiśniewski, Marcin (Int J Environ Res Public Health, 2020)
Community pharmacies are the primary entities providing drugs to individual patients in Poland. The pharmacy market has been changing for many years due to significant changes in market regulations. These changes significantly affect the profitability of pharmacies, which may impact the quality of pharmacotherapy. The small number of pharmacies, which resulted from changes in the law in 2017, can influence the level of patient care. The article presents the community pharmacies market in Poland. Particular attention is paid to the legal regulations affecting community pharmacies and the impact of these regulations on the overall shape of the market. The Polish system’s specificity, including the pharmacy market indicators, has been compared with data from other European Union countries.